(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
At the trial, a witness in normal course is given a religious book “Geeta” to take oath “I swear by Almighty God that the evidence I shall give shall be the truth, the whole truth and nothing but the truth”. The Public Prosecutor for the party who has called a witness will then ask from this witness a series of questions to allow to give his/her evidence. This is called the “examination in chief”. The questions that a witness is asked at this stage are designed to guide the witness through the evidence so that witness can give his/her account of what happened in own words. Witness should carefully consider each question and answer it truthfully. the examination in chief, the defence lawyer for the other side asks this witness a series of questions. This is called the “cross-examination”. The purpose of the cross-examination is to allow the other side to attempt to undermine or reduce the significance of the evidence.